Universities and Knowledge Economies: A paradigmatic change? - MacDonald, Gerard (Proceedings of the International Conference on Networked Learning, 2000)
Universities multiply. but have a common teaching style. There are exceptions, but most work within a model based on meeting of teacher and students - often with the teacher as lecturer - supported by published books and teachers’ notes. It is a model that can be traced back to the time. around 640BC. when students first came to Assurbanipal’s royal library at Nineveh. Central to this classical conception is the ideal of creating, evaluating. preserving and disseminating knowledge; and the condition that learners will travel to where teachers and information are - to a place called a university.